Request for material samples for the structure construction, pre-opening and pre-embedding works - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request for material samples for internal plumbing & sanitary works and internal electrification works of BRACU new campus project.